Under the Influence: Pay-Offs to Legislative Support Parties under Minority Governments. Issue 1 (10th January 2021) - Anghel, Veronica; Thürk, Maria
Abstract: Previous studies show that in multiparty systems the formation of minority governments can be a rational choice. To ensure survival and policy implementation, minority governments make concessions to non-cabinet parties. In this study, we empirically analyse the pay-offs given to support parties under minority governments. We argue that the content of support agreements is conditioned by support party type. Results are based on a two-stage empirical investigation: a text analysis of 10 explicit support arrangements for minority governments in Romania and a within-case comparison of two Romanian minority cabinets with different support arrangements. We employ an original data set of support agreements and elite interviews with former minority cabinet members. We empirically confirm that ethno-regional parties are mostly policy-seeking and target benefits for their specific groups. In contrast, mainstream parties make stronger claims for office distribution. The analysis challenges the widespread understanding that all support parties are mostly policy-seeking.